2022
DOI: 10.3389/fonc.2022.951805
|View full text |Cite
|
Sign up to set email alerts
|

Clinical determinants impacting overall survival of patients with operable brain metastases from non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) is currently the leading cause of cancer-related death worldwide, and the incidence of brain metastases (BM) in NSCLC patients is continuously increasing. The recent improvements of systemic treatment in NSCLC necessitate continuous updates on prognostic subgroups and factors determining overall survival (OS). In order to improve clinical decision-making in tumor boards, we investigated the clinical determinants affecting survival in patients with resectable NSCLC BM. A retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In fact, more than 15% of all metastatic lung adenocarcinomas exclusively affect the brain as the only organ involved, either at the time of primary diagnosis (oligo-synchronous) or after primary diagnosis (oligo-metachronous) 2 . Clinical data suggest that oligo-brain metastatic disease, often accompanied by a favorable prognosis, represents a distinct form of cancer spread compared to a disease that spreads uncontrolled to multiple sites (poly-metastatic) [4][5][6] . Several prospective studies have demonstrated significantly improved progression-free or overall survival in oligo-metastatic NSCLC patients who received stereotactic body radiotherapy, as compared to maintenance therapy alone [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, more than 15% of all metastatic lung adenocarcinomas exclusively affect the brain as the only organ involved, either at the time of primary diagnosis (oligo-synchronous) or after primary diagnosis (oligo-metachronous) 2 . Clinical data suggest that oligo-brain metastatic disease, often accompanied by a favorable prognosis, represents a distinct form of cancer spread compared to a disease that spreads uncontrolled to multiple sites (poly-metastatic) [4][5][6] . Several prospective studies have demonstrated significantly improved progression-free or overall survival in oligo-metastatic NSCLC patients who received stereotactic body radiotherapy, as compared to maintenance therapy alone [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%